Komunikasi Dalam Bisnis - Rifandi Syahputra; Nuri Aslami (VISA: Journal of Vision and Ideas, 2021)
In a business, communication is one of the important factors in the success of business achievement. The purpose of this study was to find out how to analyze communication well. This research method uses qualitative research methods, namely research that emphasizes understanding the problem through disclosure of facts obtained through interview and observation data. The result of this research is an understanding of how to communicate well. The conclusion obtained through this analysis is the process of exchanging messages or information to achievethe effectiveness and efficiency of work products in organizational structures and systems. Inbusiness communication activities, messages should not only be informative, but must also bepersuasive, so that other parties are willing to accept an understanding or belief or perform anactor activity. Keywords: communicationa nalysis, business,how to communicate